Knowledge of the international phonetic alphabet and its influence for a suitable pronunciation of consonants - Burgos Segura Diana Olinda (Machala : Universidad Técnica de Machala, 2016)
The current study pretends to give a general explanation of the importance of using the ipa, which is quite unknown by english teachers of our province, and the whole country. it can be said that it happens even in any culture where english pronunciation is a well discussed issue. many teachers neglected the knowledge of the existence of a guide for them to be able to pronounce words; that means that many representations of phonemes are letter-like symbols, which represent a grapheme. there are 24 consonants symbols. from this total, eight symbols are not letter-like. four digraphs do not have any similarity as the other letters do. the author has separated these eight phonemes and has given some examples, and individual explanation of utterance, in order to help learners, how to pronounce, related with spanish sounds. the document has detailed as well, a chart with some articulation points and the manner consonants should be articulated, and their classification as voiced and voiceless categories. in case a user of the language does not get accuracy in their utterance, then intelligibility is a good way to be heard, provided that communication go through.
Keywords: PHONEME; GRAPHEME; DIGRAPH; SYMBOL; UTTERANCE; INTELLIGIBILITY